Inertia and Managerial Intentionality: Extending the Uppsala Model - Dow, Douglas; Liesch, Peter; Welch, Lawrence (Management international review, 2018)
The Uppsala Internationalization Process Model is the most cited model within the field of international business. However, even with its most recent formulation, the model is predicated on a key set of assumptions about the limiting and releasing mechanisms in a 'change of state' decision. The model assumes that uncertainty, risk, lack of trust, and lack of awareness of opportunities are the main constraints, and that the accumulation of experiential knowledge, trust, and market commitment are the main releasing factors that allow a firm to overcome those constraints and progress to a higher state of commitment. We argue that the preceding view may be excessively narrow, and that inertia and managerial intentionality may also play a role as critical limiting and releasing mechanisms, respectively. This development implies that the passage of time and experiential learning may not always have a positive impact on firm internationalization. The extended model proposed in this paper highlights the role of the manager, and brings a contingent element to the model, thus broadening its applicability by providing new insights on issues typically considered outside the realm of the Uppsala model, such as rapidly internationalizing firms, regionalization, mode inertia and mode skipping.